(untitled) (Research, Society and Development, 2020)
Most researchers have frozen dog semen using methodologies described for other species. Consequently, these studies have shown that the thawed semen of dogs is of low quality, with conception rates lower than that of other species. Therefore, in this study, we evaluated different freezing protocols for canine semen, using three adult Bulldog Campeiro males, aged 2 to 5 years, with proven fertility. Five semen samples were collected from each animal using the penile bulb digital manipulation method. The collected samples were divided into: group 1, the samples were diluted directly in Botudog® commercial freezing medium (Botupharma Biotecnologia Animal) and group 2, the samples were centrifuged at 600 g for 10 min and the pellet was resuspended in Botudog®, totaling a concentration end of 200 x 106 sperm per ml. The samples were packaged in 0.5 mL straws at a concentration of 100 x 106 viable sperm. The samples remained for 1 h in stabilization at 4 °C and transferred to nitrogen vapor for 20 min, immersed in nitrogen, stored in a cryogenic cylinder, and thawed at 46 °C for 20 s. It was found that the total motility (MT, %), path speed (VAP, μm/s), progressive motility (PM, %), progressive linear speed (VSL; µm/s), curvilinear speed (VCL; µm/s), linearity (LIN, %), percentage of fast sperm (RAP, %), and plasma and acrosomal membrane integrity were higher in group 1, with samples not being centrifuged. These data demonstrate that the canine semen freezing protocol, using the Botudog® diluent, does not recommend the centrifugation of the ejaculate, prior to freezing.